Class acts : service and inequality in luxury hotels - Sherman, Rachel, 1970- (University of California Press, 2007)
Going behind the scenes in two urban luxury hotels, this study gives a picture of the workers who care for and cater to wealthy guests by providing seemingly unlimited personal attention. Drawing on interviews and ethnographic research in a range of hotel jobs, it analyses what exactly luxury service consists of.